Nuclear data uncertainty propagation for spectral reaction ratios. (December 2018) - Keith, Corey; Selby, Hugh; Lee, Amy
Highlights: Developed a detailed Zeus/Comet critical assembly model for IER-163. Evaluated discrepancies between experimental and modeled results. Nuclear data and experimental uncertainties were propagated through several methods. The Monte-Carlo methods provide a thorough estimate of uncertainty for the indices. Abstract: This paper describes several approaches to propagating nuclear data uncertainty in integral capture and fission reaction rates, focusing on the spectral hardness indices of 193 Ir(n, n′) 193m Ir/ 191 Ir(n, g) 192 Ir and 238 U(n, f)/ 235 U(n, f) in fast critical assemblies. Uncertainties in the nuclear data were propagated through the following methods: a sensitivity method (utilizing first order perturbation and covariance matrices), a BFMC method (random cross sections generated through covariance matrices), and Total Monte Carlo method (random cross sections generated from varying nuclear parameters). The uncertainty estimates from the three approaches are evaluated against the associated experimental uncertainties of a ZEUS/COMET critical assembly irradiation. The uncertainty estimates of the three approaches agree fairly well, and contribute a significant portion to the overall uncertainty of the spectral hardness indices.